A Flexible Two-Way PM-Based Fiber-FSO Convergence System - Chung-Yi Li; Hai-Han Lu; Wen-Shing Tsai; Xu-Hong Huang; Yun-Chieh Wang; Yong-Nian Chen; You-Ruei Wu (IEEE Photonics Journal)
This paper aims to propose and conduct a practical demonstration of a flexible two-way phase modulation (PM)-based fiber-free-space optical (FSO) convergence system employing one optical carrier transmission scheme and vertical cavity surface emitting laser (VCSEL)-based tunable optical band-pass filter (TOBPF). One optical carrier is delivered to efficaciously reduce the dispersion effect caused by a 40-km single-mode fiber (SMF) transportation and the distortion caused by beating among multiple optical sidebands. Using a VCSEL-based TOBPF at the receiving site, the selected optical signal will be acquired flexibly from one of the multiple injected optical signals. This is the first time that an optical carrier transmission scheme and a VCSEL-based TOBPF are used in a two-way PM-based fiber-FSO convergence system. The downstream light is flexibly phase-remodulated with microwave/millimeter-wave data signal for uplink delivery. In-depth observation shows that bit error rate performs brilliantly via a 40-km SMF transportation with a 100-m FSO link. Such a flexible two-way PM-based fiber-FSO convergence system would be very attractive for the integration of fiber backbone and indoor networks to provide data signal flexibly.